Perilaku Termal Baterai Kendaraan Listrik pada Siklus Mengemudi NEDC dan WLTP: Studi Simulasi Menggunakan GT-Suite - Setiawan, Yosua; Said, Mohd Farid bin Muhamad; Sutjiadi, Adrian (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2025)
This study examines the thermal behaviour of a LiFePO₄ battery pack in a converted electric vehicle using GT-Suite simulation. The base vehicle, a Toyota Avanza originally powered by a 1.3-litre engine, was retrofitted with a 60 kW synchronous AC motor and a 268.8 V, 40.32 kWh battery pack. Simulations were conducted under NEDC and WLTP driving cycles, both with and without passive cooling. Results showed that battery temperature peaked at 45.3°C (NEDC) and 71.6°C (WLTP) without cooling, and was reduced to 36.6°C and 48.0°C respectively with passive cooling. Temperature spikes coincided with rapid acceleration and high-speed phases, highlighting the influence of discharge current on battery heating. These findings demonstrate the importance of thermal management in EV conversions and the effectiveness of passive cooling. Future work will focus on experimental validation and discharge current control via a battery management system (BMS) to ensure battery safety and longevity.